Food access interventions in American Indian and Alaska Native communities - Danya Carroll; Lynn Mad Plume; Nicole Redvers (Journal of Agriculture, Food Systems, and Community Development)
American Indian and Alaska Native (AI/AN) communities in the United States represent culturally rich food landscapes and traditions. Yet, food access in AI/AN communities remains a public health issue. Food access is influenced by a myriad of factors that may interact at different levels of the social ecological model (SEM). Using a scoping review methodology, we aimed to map the existing Indigenous community food access literature in the U.S. to the SEM to identify common SEM impact leve ls that food access interventions are targeting. We further reflected on AI/AN community food access intervention gaps to inform future intervention targets. A systematic search strategy was developed and carried out in the following electronic databases with search dates from 1988 to 2023: PubMed, CINAHL, SocIndex, Academic Search Premier, ERIC, and Google Scholar. We then carried out deductive content analysis through the lens of the SEM using qualitative software. Intervention targets were identified based on what changes were highlighted in articles at each SEM level. Fourteen articles met the inclusion criteria for the review. Interventions targeted the ‘intrapersonal’ and ‘community’ SEM levels the most, while the ‘institutional’ and ‘public policy’ levels were the least targeted. Food access was promoted in various intervention formats, including supporting community and/or school gardens; providing seeds; providing traditional foods at school, family, and community events; and providing meals to families. Our review found that valuable research has been conducted on AI/AN food access interventions with many interventions targeting multiple levels of the SEM. Our review highlights the importance of leveraging strengths in AI/AN communities to enhance food access, including through culturally aligned programs and traditional foods. Further collaboration between AI/AN communities and researchers may lead to the development of more informed multilevel interventions that further integrate Indigenous methodological and culturally based approaches to improving food access.